2020
DOI: 10.3390/cells9102239
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of IgG to Induce Murine and Human Thymic Maturation of IL-10+ B Cells (B10) Revealed in a Pilot Study

Abstract: Regulatory B (B10) cells can control several inflammatory diseases, including allergies; however, the origin of peripheral B10 cells is not fully understood, and the involvement of primary lymphoid organs (PLOs) as a primary site of maturation is not known. Here, using a murine model of allergy inhibition mediated by maternal immunization with ovalbumin (OVA), we aimed to evaluate whether B10 cells can mature in the thymus and whether IgG can mediate this process. Female mice were immunized with OVA, and offsp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 51 publications
(83 reference statements)
1
12
0
Order By: Relevance
“…As theoretically discussed in 2017 with the "MatIgG primary modulation theory" (35), the passive transference of maternal IgG can modulate offspring immunity when maternal IgG reaches offspring primary organs modulating the immunity development according to maternal atopic state. This hypothesis has been confirmed with pieces of evidence obtained in murine (36,37) and translational experimental approaches (38,39).…”
Section: Discussionsupporting
confidence: 59%
“…As theoretically discussed in 2017 with the "MatIgG primary modulation theory" (35), the passive transference of maternal IgG can modulate offspring immunity when maternal IgG reaches offspring primary organs modulating the immunity development according to maternal atopic state. This hypothesis has been confirmed with pieces of evidence obtained in murine (36,37) and translational experimental approaches (38,39).…”
Section: Discussionsupporting
confidence: 59%
“…Apart from that, in the past years, some studies have demonstrated that IgG can play a pivotal role in mediating complex interactions that result in functional lymphocyte modulation during maturation in self or offspring primary lymphoid organs and how this implicates in the context of allergy (33,37,(49)(50)(51). These studies proposed several IgG idiotypes interacting with molecules expressed on B-and T-cell membranes during the maturation process, including clonal receptors (BCRs and TCRs).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in the literature demonstrated that IgG antibodies could interact with lymphocytes precursors in the murine and human thymus, modulating its cytokine production as recently revised (31). Together, these pieces of evidence suggest that atopic and non-atopic individuals' IgG repertoire can differentially modulate the maturation of thymic TCD4, TCD8, iNKT B, and γδT cells modulating or inhibiting the development of allergy (32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42). In those observations, it has become evident that IgG antibodies can interact with a wide range of clonal or conserved receptors expressed in several cell populations.…”
Section: Introductionmentioning
confidence: 87%
“…To evaluate intracellular IL-17 production, we adopted a previously standardized protocol for spontaneous cytokine production analyses for intracellular cytokine staining [ 17 , 21 , 27 , 43 ]. Briefly, thymocytes were cultured for 24 h at 3 × 10 6 cells/mL in RPMI (Gibco—ThermoFisher, Waltham, MA, USA) supplemented with 10% heat-inactivated fetal clone (FCS-III, HyClone, Logan, UT, USA) sera without stimulus and in the presence of 10 µg/mL brefeldin A (Sigma, St Louis, MO, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Some hypotheses discussed that maternal immunization with allergens could broadly modulate offspring intrathymic maturation of T cells [ 18 , 19 , 20 ] and had been experimentally evidenced for murine and human γδT, Treg and Breg cells [ 12 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. However, no molecular pieces of evidence have been obtained to elucidate if this mechanism involves some epigenetic alterations on modulated cells.…”
Section: Introductionmentioning
confidence: 99%